Импорт изделий или «импорт» традиции (в связи с новыми находками «иллирийских булавок») в Северо-Западном Причерноморье) - Носова, Л.В. (Материалы по археологии Северного Причерноморья, 2009)
This article is dedicated to spread of two-shank pins in the North-Western Black Sea area. The earliest pins come from a pit investigated in Borysthenes and from an ancient Greek burial complex on the Nikonion chora. These finds points that initially “Illyrian shaped” pins appeared evidently in Greek settlements. From Berezan they were apparently delivered to forest-steppe zone. The author examines two possible ways of appearance of these artefacts in the North-Western Black Sea colonies. The first is by way of trade (import of pieces from Phrygia or Balkans — Greece, Macedonia, Illyria); the second — with some barbarian group of cultural tradition-carri-ers (perhaps, thraco-illyrian origin) which following the Greeks from the North-Eastern Dobrudja cities (Istria) arrived to the Greek settlement of Boristhen and one of Nikonion. In spite of the fact that the first conception is more traditional and demonstrable, the author gives her attention to the hypothesis of migration, not popular and hard to prove. The guess route — through the Thracian hinterland and Western Pontic colonies to the colonies on the North-Western Black Sea Coast — may explain the absence of two-shank pins in the area to the East of Dnieper.